Carbon fluxes in a mediterranean reservoir under a scenario of changing hydrology - Montes-Pérez, Jorge (UMA Editorial, 2023)
Inland waters have been related to human development from ancient times supporting us with a wide range of ecosystem services. Recently, it has been highlighted the key role that these systems play in the global carbon cycle becoming a key element in weather regulation and climate change mitigation policies. Within inland waters, reservoirs have been reported as one of the most active compartments in the global carbon cycle. The number of reservoirs is in expansion due to population growth, linked to an increase in water and energy demand. Besides that, climate change and direct anthropogenic pressures (irrigation, water diversion, aquifer overexploitation, land use changes, etc.) trigger alterations in hydrology and thermal structure which could modify carbon fluxes in aquatic ecosystems. Furthermore, the last report of IPCC (AR6) points out the Mediterranean region as one of the most affected by these pressures. Although there has been an important improvement in the scientific knowledge about carbon fluxes in reservoirs, there is still a lack of information due to its high spatial and temporal variability and this is especially conspicuous for Mediterranean ecosystems. Therefore, more research is necessary to understand the effects of hydrological and thermal structure changes on carbon fluxes in Mediterranean reservoirs in order to be able to improve predictions and anticipate and reduce climate changes effects. This thesis tackles the effect of hydrological and thermal structure changes in carbon fluxes in a Mediterranean reservoir (El Gergal, Seville) measuring both CO₂ and CH₄ fluxes from water surface, CO₂ fluxes from drawdown areas and the accumulation of CO₂ and CH₄ in the hypolimnion.
The reservoir ecosystem was a sink of CO₂ during the stratification period, meanwhile it was a source during the mixing period. On the contrary, CH₄ emissions were higher during mixing period, especially relevant in the riverine zone and through the ebullitive via. Drawdown area was a source of CO₂ to the atmosphere with mean flux of 196 mmol·m²·d⁻¹. Hypolimnion accumulated CO₂ and CH₄ during thermal stratification, and the magnitude of these greenhouse gases production was related to stratified period length. Therefore, longer stratification periods could lead to higher accumulation of dissolved inorganic carbon and CH₄, as well as other reduced substances (such as H₂S or metals), impairing water quality. In an annual balance, El Gergal reservoir constituted a net carbon emitter (~600 t C·yr⁻¹) and resulting in ~800 t CO₂ eq·yr⁻¹ of Global Warming Potential (GWP). GWP was higher during the thermally stratified period mainly due to a higher CH₄ production and a higher drawdown area surface. In terms of C, CO₂ was the most relevant element in the annual balance of El Gergal reservoir. Nevertheless, CO₂ emission from drawdown areas and CH₄ emissions were the most important contributors to GWP of the reservoir. Hydrological (such as water level fluctuation and water renewal rate) as well as thermal structure changes (i.e. stratification length) had a negative impact on water quality and carbon footprint of the reservoir. In the present scenario of global change, it is necessary to take into consideration these results in order to reduce impairing water quality and carbon footprint of reservoirs.
Keywords: Hidrología - Tesis doctorales; Carbon; Ddioxide; Methane; Hypolimnion; Drawdown; Water; Surface